The prevalence and nutritional causes of hypoglycaemia in patients with end-stage renal failure (ESRF) on maintenance haemodialysis (MHD) at Kenyatta National Hospital Nairobi, Kenya - Kariuki, Anastacia Wanjiku (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2008.